A. Pinzani. Towards a Kantian Argument for a Universal Basic Income / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The paper defends that it is possible to offer a Kantian argument for justifying the introduction of Universal Basic Income (UBI). It first briefly presents Philippe van Parijs’ argument for UBI based on the concept of real freedom for all. In doing so, it will focus on its general structure and central insight, without entering too much into other issues like the economic feasibility of UBI. It second briefly presents Kant’s concept of external freedom and especially focuses on some of its components to assess whether there is some closeness to van Parijs’ concept of real freedom. It further considers whether UBI is not only compatible with a Kantian position, but can be justified from such a position because it represents a tool for concretely realizing external freedom as presented in the Doctrine of Right and for attaining the ethical ideal of virtuosity presented in the Doctrine of Virtue.